Outcomes of exclusive radiation therapy for older women with breast cancer according to age and comorbidity status: An observational retrospective study. Issue 5 (14th February 2020) - Cao, Kim I.; Waechter, Lorraine; Carton, Matthieu; Kirova, Youlia M.
Abstract: The management of older patients with breast cancer, a public health issue, remains a highly topical subject. Among this heterogeneous population, only few studies have focused on outcomes of older women treated with exclusive radiation therapy for localized BC. This retrospective study provides data concerning the efficacy and safety of exclusive RT, as well as the impact of comorbidities according to the Charlson Comorbidity Index on survival in this subset of women not suitable for surgery or who have refused it. This analysis demonstrates that this treatment is well‐tolerated; however, the prognosis is strongly impacted by age and comorbidities.